A NanoLuc Luciferase Reporter Pseudorabies Virus for Live Imaging and Quantification of Viral Infection - Wang, Yalin; Wu, Hongxia; Wang, Bing; Qi, Hansong; Jin, Zhao; Qiu, Hua-Ji; Sun, Yuan (Frontiers in Veterinary Science, 2020)
Pseudorabies (PR), also known as Aujeszky's disease, is an acute infectious disease of pigs, resulting in significant economic losses to the pig industry in many countries. Since 2011, PR outbreaks have occurred in many Bartha-K61-vaccinated pig farms in China. The emerging pseudorabies virus (PRV) variants possess higher pathogenicity in pigs and mice than the strains isolated before. Here, a recombinant PRV (rPRVTJ-NLuc) stably expressing the NanoLuc (NLuc) luciferase fusion with the red fluorescent protein (DsRed) was constructed to trace viral replication and spread in mice. Moreover, both DsRed and NLuc luciferase were stably expressed in the infected cells, and there was no significant difference between wild-type and recombinant viruses in both growth kinetics and pathogenicity. 7-week-old BALB/c mice were infected with 103 TCID50 rPRVTJ-NLuc and subjected to daily imaging. The mice infected with rPRVTJ-NLuc displayed robust bioluminescence that started 4 dpi, bioluminescence signal increased over time, peaked at 5 dpi, remained detectable for at least 6 dpi and disappeared at 7 dpi, meanwhile the increased flux accompanied by the spread of virus from injection site to superior respiratory tract. However, signal was also observed in the spinal cord, trigeminal ganglion and partial region of the brain from separated tissues, not in living mice. Our results depicted a new approach to rapidly access the replication and pathogenicity of emerging PRVs in mice.